Anne tutumlarının 5-6 yaş çocuklarının sosyal becerilerini ve Okula uyumlarını yordayıcı etkisi - (:unkn) unknown (My University, 2013)
Araştırmanın amacı, anne tutumlarının çocuklarının sosyal becerileri ve okula uyumları üzerindeki yordayıcı etkisini ortaya koymaktır. Araştırmada ilişkisel tarama yöntemi kullanılmıştır. Araştırmanın örneklem grubunu Denizli ilinin merkez ilçesinde ilköğretim okullarının anasınıflarına devam eden 85 çocuk ve annesi oluşturmuştur. Araştırmada veri toplama araçları olarak Anne-Babalık Stilleri ve Boyutları Ölçeği (Anne formu), Sosyal Beceri Formu ve 5-6 Yaş Çocukları İçin Okul Uyumu Öğretmen Değerlendirme Ölçeği kullanılmıştır. Araştırmanın sonuçlarına göre, annelerin otoriter, yetkeci ve izin verici tutumları ile 5-6 yaşındaki çocuklarının sosyal beceri ve okula uyum düzeyleri arasında anlamlı düzeyde ilişki belirlenmiştir. Otoriter ve izin verici tutumlar, sosyal beceri ve okula uyum değişkenleri ile olumsuz yönde anlamlı ilişki içindeyken; yetkeci tutum ise sosyal beceri ve okula uyum düzeyleri ile olumlu yönde anlamlı ilişki içindedir.

The purpose of this study is to put forth the predictor effect mother’s attitude has on the social skills and school adaptation of their children. A relational survey method was used in this study. The sample group for the study comprised of 85 children, attending the kindergartens of primary schools located in the city center of Denizli, and this children’s mother. The Parenting Styles and Dimensions Questionnaire (PSDQ) (Mother Form), Social Skills Form and The Teacher Rating Scale of School Adjustment for 5-6 Year Olds were used to gather the data for the study. According to the results of the study, there is a significant relationship between the authoritarian, permissive, and authoritative mother attitude and the level of social skills and school adjustment in 5-6 year old children. While there is a significant negative relationship between authoritarian and permissive attitudes and the social skills and school adjustment variables, a significantly positive relationship exists between authoritative attitude and the level of social skills and school adjustment. Parental attitude expresses the quality of special behavior patterns and approaches of parents towards their children. Temperament, the tone of voice used towards the child, body language, the nature of interest, attention, care, and childcare-related experiences carry great importance when establishing the attitude (Bornstein & Zlotnik, 2009). During the early years of life, parents have a greater influence over their child’s life than other people. Positive and supportive attitudes are factors with powerful effects in child development (Eisenberg et al., 2005; Gülay, 2010). In conclusion of her studies, Diana Baumrind put forth three basic parental attitudes; Authoritarian, Authoritative, and Permissive (Baumrind, 1966, 1967, 1968, 1978, 1976).In the authoritarian attitude, parents place importance on controlling their children and making sure their children listen to them. Authority, rule acceptance, and respect must be shown in all forms. While interest in the child is minimum, the expectations from the child are maximum. Issues experienced regarding the rules in the adult world may result in severe penalties (Baumrind, 1967; Bornstein & Zlotnik, 2009). The authoritative attitude is shaped with democracy, respect, and rationale. The individuality of child is accepted and respected. Accepting individuality means that they have a say in the decisions made at home. The type of communication between the child and their parents is mutual and open. The child’s independence is supported. Authoritative parents believe that severe and physical punishments damage the individuality and personality of the child (Johnson, 2006; Weiten, Lloyd, Dunn, & Hammer, 2009). On the other hand, permissive attitude is based on extensive child care, open communication, and minimal control. The rules and limits are not distinct but are very flexible. The expectation of mature behavior from the child is minimal. The attitude towards the child’s behavior, even if it involves aggression, is extremely tolerant. The approach is loose in terms of discipline (Feldman, 2005; Maccoby & Martin, 1983). The effects these attitudes have on children vary. Purpose The purpose of this study is to put forth the predictor effect mother’s attitude has on the social skills and school adaptation of their children. We searched for the answers to the questions stated below in an effort to achieve the purpose of this study. Does an authoritarian attitude of mother have a predictor effect on the social skills and school adjustment of 5–6 year old children? Does an authoritative attitude of mother have a predictor effect on the social skills and social adjustment of 5–6 year old children? Does a permissive attitude of mother have a predictor effect on the social skills and school adjustment of 5–6 year old children? Method A relational survey method was used in this study. The sample group for the study comprised of 85 children, attending the kindergartens of primary schools located in the city center of Denizli, and this children’s mothers. The Parenting Styles and Dimensions Questionnaire (PSDQ) (Mother Form), Social Skills Form and The Teacher Rating Scale of School Adjustment for 5-6 Year Olds were used to gather the data for the study. The Parenting Styles and Dimensions Questionnaire (PSDQ) (Mother Form) was completed by mothers individually. Social Skills Form and The Teacher Rating Scale of School Adjustment for 5-6 Year Olds was completed by kindergarten teachers based on their 7-month observation of the children. Mothers and teachers were informed about the purpose of the study and the measurement instruments prior to the data collection process. Data was analyzed using a SPSS 13.0 software program. A Simple Linear Regression Analysis Technique was used to determine a predictor effect of authoritarian, permissive, and authoritative mother attitudes on the social skills and school adjustment of 5–6 year old children. Findings According to the results of the study, there is a significant relationship between the authoritarian, permissive, and authoritative mother attitude and the level of social skills and school adjustment in 5-6 year old children. While there is a significant negative relationship between authoritarian and permissive attitudes and the social skills and school adjustment variables, a significantly positive relationship exists between authoritative attitude and the level of social skills and school adjustment. Authoritarian, authoritative, and permissive attitudes at maximum level explain school adjustment. While authoritarian attitude explains school adjustment and social skills at the highest level, permissive attitude was one that explains school adjustment and social skills at the lowest level. Discussion & Conclusion In general, the positive and adverse attitude of mothers towards their children has a positive or adverse effect on the social skills and school adjustment of children. When mothers are harsh on their children because of their authoritarian attitude, and give them severe punishments, are not adequately sensitive towards their desires and feelings, they set an adverse example in terms of social skills. The authoritarian attitude, based on punishment, severity, and strict rules, has an adverse effect on the school adjustment of children. The strict rules and strict discipline at home may make it difficult for children to comply with the rules at school. In a similar way, the permissive attitude may adversely affect children learning social skills at school as the rules and limits are not distinct and/or are very flexible. As a result, children may not exhibit the care expected to successfully maintain the social relations and abide by the rules at school or within their peer groups, as they do so at home. The authoritarian attitude may result in children being shy and unsocial, as well as displaying aggressive and domineering behaviors. These children being socially less adaptable, and having lower self-confidence attracts attention. Children, who have parents that do express their emotions accordingly, may portray harsh responses to their peers in case of angry or bitter. Similarly, children, who have parents that express generally their positive emotions, are able to control their emotions in their social relationships (Eisenberg et al., 2005). A different situation exists for the authoritative attitude. With this attitude, the child sees positive examples at home in relation to obeying the rules, being sensitive towards other, being empathic, helping one another, and working as a team. Thus, the child gains positive experiences in terms of social skills. Bornstein and Zlotnik (2009) expressed that authoritative parents set positive examples for their children in terms of conserving their self-control in stressful situations, and stated that this affect healthfully the child’s peer relations. Secondly, the language and cognitive skills which develop thanks to the open communication with the child support competencies such as managing social relations and correct analysis of social situations. The fact that the rules are explained to the child, their views are respected, and they are given a say when decisions are made helps them to become aware of their individuality within the social system. In addition, children display the same positive behavior they have witnessed from their parents in similar situations within their peer group (Kochanska & Aksan, 2004; Macklem, 2008). Various seminars and training courses should be offered to families on the subject of bringing up children by organizations and institutes such as pre-school education organizations, Public Education Centers, Municipalities, and Universities, in line with effects of mother’s attitude on the social skills and school adaptation of children. Education organizations should be in constant contact with parents during family participating activities. Social relation issues experienced by children must be resolved working in collaboration with their families.
The predictor effect of attitudes of mothers on the social skills and school adaptation of their 5–6 year old children